Dual effects of α2‐adrenoceptors in modulating myogenic tone in sheep isolated internal anal sphincter. Issue 8 (6th June 2014) - Rayment, S. J.; Simpson, J. A. D.; Eames, T.; Acheson, A. G.; Dashwood, M. R.; Henry, Y.; Gruss, H.; Scholefield, J. H.; Wilson, V. G.
Abstract Background The role of α‐adrenoceptors in promoting continence through modulation of sphincter tone has focused primarily on the effects of α1‐adrenoceptors. We have used three clinically available agents, which are selective for α2‐adrenoceptors, to investigate their role in contractile and neurogenic responses on the internal anal sphincter (IAS). Methods IAS strips, which had spontaneously generated tone, were used to investigate the contractile effect of lofexidine, brimonidine, and dexmedetomidine on muscle tone in the presence or absence of subtype selective antagonists. The effect of brimonidine on the magnitude and time course of neurogenic responses generated by electrical field stimulation (EFS) was also examined. The affinity of test compounds at α1‐ and α2‐adrenoceptors was established by competition binding with [3H]‐prazosin and [3H]‐RX821002. Key Results All agonists caused concentration‐dependent contraction of the IAS and lofexidine demonstrated an enantiomeric difference in potency with a 10‐fold difference between the (−) and (+) isomers. Responses to lofexidine and dexmedetomidine were inhibited in the presence of the α1‐adrenoceptor selective antagonist prazosin, but not in the presence of RX811059 (α2‐adrenoceptor selective antagonist); brimonidine responses were inhibited by RX811059 and, to a lesser extent, by prazosin. Brimonidine affected both magnitude and duration of neurogenic responses, which was reversed in the presence of RX811059. Conclusions & Inferences We conclude that α2‐adrenoceptors can mediate contraction of IAS, although this effect is most evident with efficacious imidazoline agonists rather than the most selective ligand. In addition, this receptor subtype can directly inhibit noradrenergic contractile responses to EFS and, indirectly, enhance nitrergic relaxatory responses.